MENINGKATKAN MOTIVASI BELAJAR SISWA SD MELALUI BIMBINGAN BELAJAR DI DUSUN GOMBONG KABUPATEN MAGELANG - Arvina Istiqomah; Nailatul Muna (Institut Agama Islam Syubbanul Wathon Magelang, 2021)
Online learning provides a new experience for students who usually enjoy face-to-face lessons. This makes students have more free time, which is generally only actualized into less useful activities such as playing gadgets too often. The purpose of this service is to optimize students' free time and also to help students understand material that was previously difficult to understand. The method used in this study is ABCD (Asset Based Community Development). The assistance provided in tutoring activities is expected to help students understand the material obtained from school. The conclusion of this service is that students enjoy the learning process at the tutoring place, but students are not able to focus properly because they like to play with friends and mentors.